Analisis Yuridis Penerapan Prinsip Transparansi Good Corporate Governance Dalam Laporan Tahunan Berdasarkan Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas (Studi Kasus Pt Indofarma Tbk) - Aprilla Laura Utari; Robi Syafwar (CV. ITTC INDONESIA, 2026)
This research is motivated by the importance of implementing the principle of transparency in Good Corporate Governance (GCG) as a manifestation of legal certainty and accountability in the management of Limited Liability Companies as regulated under Law Number 40 of 2007 concerning Limited Liability Companies, particularly in the preparation and submission of annual reports. Furthermore, there have been findings of alleged financial statement manipulation at PT Indofarma Tbk, which indicate discrepancies between practice and the applicable legal provisions. This study aims to examine the legal regulation of the principle of transparency in annual reports based on the Company Law and to analyze the conformity of the presentation of PT Indofarma Tbk’s annual reports with the transparency principle of GCG. This research employs a normative juridical method with a statutory approach and a case approach. The research is descriptive-qualitative in nature and utilizes secondary data consisting of primary, secondary, and tertiary legal materials, which are analyzed qualitatively. The results of the study indicate that Articles 66 and 67 of the Company Law clearly regulate the obligation of the Board of Directors to prepare and submit annual reports in a complete and accurate manner, duly signed by all members of the Board of Directors and the Board of Commissioners as a form of legal responsibility. However, in practice, the presentation of PT Indofarma Tbk’s annual reports does not reflect the principle of transparency due to indications of irregularities and inconsistencies in financial information that may potentially harm shareholders and the public. In addition, Article 97 of the Company Law stipulates that the Board of Directors bears full responsibility for the management of the company and is personally liable for any losses incurred by the company if such losses result from fault or negligence in the performance of their duties. In conclusion, although normatively the regulation of the transparency principle under the Company Law provides an adequate legal foundation, its implementation still requires stricter supervision and enforcement of the legal responsibilities of the Board of Directors and the Board of Commissioners to ensure the realization of good corporate governance and the protection of stakeholders.